Posttreatment Imaging of the Knee: Cruciate Ligaments and Menisci - Heuck, Andreas; Woertler, Klaus (Seminars in Musculoskeletal Radiology, 2022)
Cruciate ligament reconstruction and meniscal surgery are frequently performed for restoration of knee joint stability and function after cruciate ligament and meniscus injuries, and they contribute to the prevention of secondary osteoarthritis. In cruciate ligaments, the most common procedure is anterior cruciate ligament (ACL) reconstruction. Meniscal surgery most frequently consists of partial meniscectomy and suture repair, rarely of a meniscus transplant. In patients with symptoms following surgery, imaging reevaluation for a suspected intra-articular source of symptoms is indicated and mainly consists of radiography and magnetic resonance imaging. For proper imaging assessment of cruciate ligament grafts and the postoperative meniscus, it is crucial to understand the surgical techniques applied, to be familiar with normal posttreatment imaging findings, and to be aware of patterns and specific findings of recurrent lesions and typical complications. This article presents an updated review of the techniques and the imaging of cruciate ligament reconstruction and meniscus surgery, recurrent lesions, treatment failure, and potential complications.
Keywords: knee; ligaments; menisci; cruciate ligament reconstruction; meniscus repair; magnetic resonance imaging; computed tomography